2023
DOI: 10.1111/1752-1688.13119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of compost amendment rate and level of compaction on the hydraulic functioning of soils

Abstract: There has been widespread interest in using compost to improve the hydrologic functions of degraded soils at construction sites for reducing runoff and increasing infiltration. The objective of this study was to determine the effects of compost amendment rate on saturated hydraulic conductivity (Ks) and water retention in order to identify target compost rates for enhancing soil hydrologic functions. Samples were prepared with three soil textures (sandy loam, silt loam, and sandy clay loam), amended with compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Finally, compost appeared to be more effecive in fine‐textured soils than course‐textured soils, similar to other studies (Aggelides & Londra, 2000; Kranz et al., 2022, 2023; Mohammadshirazi et al., 2017). Kranz et al.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, compost appeared to be more effecive in fine‐textured soils than course‐textured soils, similar to other studies (Aggelides & Londra, 2000; Kranz et al., 2022, 2023; Mohammadshirazi et al., 2017). Kranz et al.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, compost appeared to be more effecive in fine-textured soils than course-textured soils, similar to other studies (Aggelides & Londra, 2000;Kranz et al, 2022Kranz et al, , 2023Mohammadshirazi et al, 2017). Kranz et al (2023) found that 20%-50% compost by volume was needed to increase infiltration depending on the soil texture. Compost application needs to be optimized to site-specific soil characteristics to be an effective soil amendment for post-contruction soil restoration.…”
Section: Implications and Challengessupporting
confidence: 88%
See 1 more Smart Citation
“…Although compost can increase WHC due to its high organic matter content, its application does not necessarily affect PAW. Moreover, Kranz et al [84] reported that when sandy and silt loam soils with medium porosity were amended with high levels of compost, in some cases they would show NE on PAW. Also, they showed that a significant increase in PAW can occur after applying compost to sandy clay loam and high-porosity sandy loam soils.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%